Efficient elimination of Yam mosaic virus (YMV) from white yam (Dioscorea rotundata Poir.) by cryotherapy of axillary buds - Ita, E.E.; Uyoh, E.A.; Nakamura, I.; Ntui, V.O. (Elsevier, 2019)
Dioscorea rotundata is an economically important food crop in many tropical countries as many people in this region depend on it for food and livelihood. Viral diseases, especially Yam mosaic virus (YMV), constitute a major constraint in the cultivation of this crop as they perpetuate through generations in the vegetatively propagated planting materials. Getting resistant or at least virus-free planting materials for farmers thus becomes crucial. This study was aimed at eliminating YMV in Dioscorea rotundata by cryotherapy of axillary buds. Enlarged axillary buds of YMV-infected TDr 2269 were frozen in liquid nitrogen for 1 h, re-warmed at 40 °C and cultured to regenerate plantlets. Approximately 76.33% plantlet regeneration and 100% YMV eradication were obtained for cryo-treated buds, against 95% and 0% obtained respectively for non-treated buds. RT-PCR and RT-qPCR analyses did not reveal detectable quantity of YMV in treated plants but did in control plants. Plants from cryo-treated buds showed no mosaic symptoms and produced slightly more tubers, and heavier mini-tubers (20.48±3.11 g) under greenhouse conditions contrary to non-treated plants that showed severe mosaic symptoms with significantly smaller tubers (1.91±0.39 g) (P < 0.05). This is the first report showing the elimination of YMV from infected white yam stock plant by cryotherapy and would be useful for producing clean planting materials.